Detecting and characterizing new endofungal bacteria in new hosts: Pandoraea sputorum and Mycetohabitans endofungorum in Rhizopus arrhizus - Liu, Xiao-Ling; Zhao, Heng; Wang, Yi-Xin; Liu, Xin-Ye; Jiang, Yang; Tao, Meng-Fei; Liu, Xiao-Yong (Frontiers in Microbiology, 2024)
The fungus Rhizopus arrhizus (=R. oryzae) is commonly saprotrophic, exhibiting a nature of decomposing organic matter. Additionally, it serves as a crucial starter in food fermentation and can act as a pathogen causing mucormycosis in humans and animals. In this study, two distinct endofungal bacteria (EFBs), associated with individual strains of R. arrhizus, were identified using live/dead staining, fluorescence in situ hybridization, transmission electron microscopy, and 16S rDNA sequencing.The roles of these bacteria were elucidated through antibiotic treatment, pure cultivation, and comparative genomics. The bacterial endosymbionts, Pandoraea sputorum EFB03792 and Mycetohabitans endofungorum EFB03829, were purified from the host fungal strains R. arrhizus XY03792 and XY03829, respectively.Notably, this study marks the first report of Pandoraea as an EFB genus. Compared to its free-living counterparts, P. sputorum EFB03792 exhibited 28 specific virulence factor-related genes, six specific CE10 family genes, and 74 genes associated with type III secretion system (T3SS), emphasizing its pivotal role in invasion and colonization. Furthermore, this study introduces R. arrhizus as a new host for EFB M. endofungorum, with EFB contributing to host sporulation. Despite a visibly reduced genome, M. endofungorum EFB03829 displayed a substantial number of virulence factor-related genes, CE10 family genes, T3SS genes, mobile elements, and significant gene rearrangement. While EFBs have been previously identified in R. arrhizus, their toxin-producing potential in food fermentation has not been explored until this study. The discovery of these two new EFBs highlights their potential for toxin production within R. arrhizus, laying the groundwork for identifying suitable R. arrhizus strains for fermentation processes.